Analysis of Some Factors Affecting Foreign Investment in The Manufacturing Industry East Java - Ayu Anggela Rinjani Putri; Marseto Marseto; Sishadiyati Sishadiyati (Journal Research of Social Science, Economics, and Management, 2021)
The industrial sector is a sector that plays a vital role in economic development because it can increase economic growth. The industrial sector also plays a role as a factor productive in maximizing the development of the industrial sector marked only by the volume of production but by an increase in various products produced. This study aims to determine the factors that influence investment mode; results in the East Java manufacturing industry. This research method uses secondary data collected from the Central Statistics Agency of East Java Province. The population in the study is data on foreign investment, manufacturing business units, foreign exchange rates, and inflation, and the data used as a sample is annual data (time series). Data collection techniques using documentation and library studies. The data analysis technique used in this research is multiple linear regression. The survey results show that manufacturing industries, foreign exchange rates, and inflation significantly affect the foreign investment variable simultaneously. In contrast, partially, manufacturing industries and inflation have no significant positive impact on foreign investment. In contrast, the foreign exchange rate has a significantly positive effect on foreign investment.